Pola Hidup Sehat dan Aktivitas Fisik Siswa Pondok Pesantren - Zaki Abdul Aziz; Yati Ruhayati; Jajat Jajat (Universitas Negeri Surabaya, 2026)
Background: Physical activity is recognized as an important determinant of adolescent health; however, the relationship between physical activity levels and a healthy lifestyle does not always show a consistent pattern across different environmental contexts. This study aimed to analyze the relationship between physical activity and healthy lifestyle among boarding school students. Methods: A cross-sectional design was employed, involving 40 twelfth-grade students residing at Al-Masoem Islamic Boarding School. Physical activity was measured using the Global Physical Activity Questionnaire (GPAQ), while healthy lifestyle was assessed with the Health-Promoting Lifestyle Profile II (HPLP-II). Data analysis included descriptive statistics, Spearman correlation tests, and comparisons based on gender, body mass index, and frequency of returning home. Results: he results indicated a significant and strong positive relationship between physical activity and overall healthy lifestyle. However, differences in physical activity by gender were not accompanied by differences in healthy lifestyle, and no significant differences were found based on body mass index categories or frequency of returning home. Conclusions: These findings suggest that high physical activity in the boarding school environment is largely influenced by institutional structure and does not fully reflect the internalization of a healthy lifestyle. The study emphasizes the importance of health promotion approaches that consider environmental context and psychosocial factors to support sustainable healthy behaviors among adolescents. Keywords: Physical activity; Healthy lifestyle; Structured environment; Islamic boarding school; Adolescent.